Síntese e caracterização de heteroestruturas de Ag2CrO4:Ag2MoO4 e de Ag2CrO4:Ag2WO4 com propriedades fotocatalíticas - Silva, Joyce Marina Paiva da (2022)
The disposal of organic pollutants, carried out incorrectly in industrial effluents, has been increasing society's interest in developing materials with photocatalytic properties that are capable of degrading these organic contaminants, such as dyes, medicines, among others. In this work, the synthesis by coprecipitation at 70ºC was used to obtain heterostructures of Ag2CrO4:Ag2MoO4 and Ag2CrO4:Ag2WO4, in which Mo and W were inserted in the proportions of 0; 0.25; 0.5; 0.75 and 1 mol% in the structure of silver chromate. The nanoparticles obtained were characterized by X-ray diffraction (XRD), Raman spectroscopy, field emission scanning electron microscopy (FESEM), high-resolution transmission electron microscopy (HRTEM) and ultraviolet visible spectroscopy (UV-Vis). For the photocatalytic properties, tests were performed against methylene blue dye and against a mixture of dyes. The XRD results confirmed the achievement of the investigated phases and Raman spectroscopy revealed significant changes in the local order-disorder as a function of the gradual replacement of the lattice former. The images obtained by FESEM and HRTEM indicated that the samples composed of two phases presented a morphology formed by the mixture of the respective pure phases and indicated the formation of heterostructures by the presence of a heterojuction. All heterostructures obtained showed absorption for longer wavelengths, and lower gap energies, when compared to pure Ag2MoO4 and Ag2WO4 phases. The photocatalytic activity was investigated and the results indicated that all samples showed good catalytic activity against methylene blue, and all heterostructures were more efficient than pure Ag2MoO4 and Ag2WO4 phases, with efficiency of 95% and 99%, respectively. The reuse cycles indicated high potential for practical application in wastewater, due to the capacity of consecutive cycles for photodegradation.